2020
DOI: 10.1038/s41467-020-16052-8
|View full text |Cite
|
Sign up to set email alerts
|

Somatic SF3B1 hotspot mutation in prolactinomas

Abstract: The genetic basis and corresponding clinical relevance of prolactinomas remain poorly understood. Here, we perform whole genome sequencing (WGS) on 21 patients with prolactinomas to detect somatic mutations and then validate the mutations with digital polymerase chain reaction (PCR) analysis of tissue samples from 227 prolactinomas. We identify the same hotspot somatic mutation in splicing factor 3 subunit B1 (SF3B1R625H) in 19.8% of prolactinomas. These patients with mutant prolactinomas display higher prolac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 28 publications
2
50
1
2
Order By: Relevance
“…A single patient with a de novo missense germline NR3C1 mutation associated with an ACTH-PA has also been described ( 138 ), while a child with corticotroph adenoma and partial glucocorticoid resistance had no detectable NR3C1 mutation ( 140 ). A recent study reported a novel somatic recurrent (“hotspot”) mutation in splicing factor 3 subunit B1 (p.R625H in SF3B1 ) in about 20% of prolactinomas in altogether 227 prolactinomas ( 141 ). This variant causes aberrant splicing of the estrogen related receptor gamma (ESRRG), causing stronger activation of PIT-1 leading to prolactin secretion and lactotroph proliferation.…”
Section: Genetic Mechanisms Of Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…A single patient with a de novo missense germline NR3C1 mutation associated with an ACTH-PA has also been described ( 138 ), while a child with corticotroph adenoma and partial glucocorticoid resistance had no detectable NR3C1 mutation ( 140 ). A recent study reported a novel somatic recurrent (“hotspot”) mutation in splicing factor 3 subunit B1 (p.R625H in SF3B1 ) in about 20% of prolactinomas in altogether 227 prolactinomas ( 141 ). This variant causes aberrant splicing of the estrogen related receptor gamma (ESRRG), causing stronger activation of PIT-1 leading to prolactin secretion and lactotroph proliferation.…”
Section: Genetic Mechanisms Of Tumorigenesismentioning
confidence: 99%
“…This is consistent with their generally low proliferation rate. Only a handful of genes show recurrent mutations ( 120 , 141 , 169 ). Such recurrently mutated genes are reported in more detail in Table 3 .…”
Section: Genetic Mechanisms Of Tumorigenesismentioning
confidence: 99%
“…These mutations are also present in 20% of patients with myelodysplastic/myeloproliferative neoplasm (MDS/MPN) [ 41 ] and in 15% of patients with chronic myeloid leukemia (CLL) [ 58 60 ] . More recently, SF3B1 mutations have been identified at relatively high frequency in some solid tumors, such as various pigmented tumors, including uveal melanoma (UM) [ 61 , 62 ], mucosal melanoma [ 63 ], leptomeningeal melanoma [ 64 ] and blue nevus-like cutaneous melanoma [ 65 ], and neuroblastomas that arise following chromothripsis [ 66 ], estrogen receptor-positive breast cancers (BC) [ 67 ], pancreatic ductal adenocarcinoma [ 68 ], prostate cancer [ 69 ], prolactinomas [ 70 ], acute myeloid leukemia [ 71 , 72 ], and many others [ 73 75 ].…”
Section: Sf3b1 Mutations In Cancermentioning
confidence: 99%
“…Mario et al found gonadotroph signatures in some corticotroph and somatotroph PitNETs by integrated pangenomic analyses [4]. The low mutation burdens of PitNETs based on WGS suggesting a limited impact of SNVs on the PitNET classi cations [20,29,30]. In this study, we found that expression at the DLK1/MEG3 locus played a key role in the differentiation of PitNETs in patients depending on the level of PIT1, and we suggested that DLK1 may be used in addition to the current array of PitNET classi cations.…”
Section: Discussionmentioning
confidence: 99%